2019
DOI: 10.1007/s00264-019-04443-6
|View full text |Cite
|
Sign up to set email alerts
|

Modified split tendon transfer of posterior tibialis muscle in the treatment of spastic equinovarus foot deformity: long-term results and comparison with the standard procedure

Abstract: Introduction Split tendon transfer of tibialis posterior (SPOTT) is a treatment option for the hindfoot varus deformity in patients with cerebral palsy (CP). The purpose of this study was to present the long-term results of the newly modified SPOTT procedure developed by our senior author and compare it with the standard SPOTT technique in equinovarus foot deformity due to CP. Method Our retrospective cohort study included patients with spastic foot deformity due to CP treated with the standard or modified SPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…equinovarus vs varus), 17 , 29 intervention (i.e. modified SPLATT vs standard SPLATT or SPLATT vs SPOTT), 13 , 15 and type of CP (i.e. hemiplegia vs diplegia).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…equinovarus vs varus), 17 , 29 intervention (i.e. modified SPLATT vs standard SPLATT or SPLATT vs SPOTT), 13 , 15 and type of CP (i.e. hemiplegia vs diplegia).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (205 feet) implemented the SPLATT intervention, 7 - 14 of which three studies were published in 2020 or, more recently, 7 - 9 implementing the SPLATT to Peroneus Brevis/Peroneus Tertius approach versus the SPLATT to cuboid approach (used in studies prior to 2015). Ten studies implemented SPOTT (353 feet), 4 , 5 , 12 , 13 , 15 , 17 , 29 , 37 - 39 with the majority reporting the SPOTT to Peroneus Brevis surgical approach. Out of these studies, two reported either SPLATT or SPOTT intervention groups depended on the clinical presentation, 12 , 13 and one had a subgroup combining both procedures during index operation (n = 3 feet).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations